Robust and Imperceptible Image Watermarking by DC Coefficients Using Singular Value Decomposition - Christy Atika Sari; Eko Hari Rachmawanto; De Rosal Ignatius Moses Setiadi (IAES Indonesia Section, 2017)
Main problem frequently encountered in all schemes transform domain watermarking technique is the robustness and imperceptibility. Due to achieved optimal result most algorithms of image watermarking using combination two or more transformation domain. This paper proposed Discrete Cosine Transform (DCT) and Singular Value Decomposition (SVD) to embed binary watermark to color Image. Before the message embedded in the color images, we converting RGB to YCbCr color space. Luminance component will be split into sub- block and it has been transformed by DCT to produce DC and AC coefficients. DC coefficients selected as embedding place because it is perceptually usefulness and robust against various attacks. DC coefficients will be collected from every sub-block to create a reference image. Then apply SVD on reference image and embed message in singular values. Various attacks have been implemented and tested due to achieve robustness using Normalized Cross Correlation (NCC) and imperceptibility tested using Peak Signal to Noise Ratio (PSNR). High values of the measurement results show the feasibility of the proposed method. A highest PSNR value resulted 42.3009 dB, whereas a highest NCC values 0.9993 after JPEG Compression.